Digoxine reduces thermal pain threshold and neuromuscular coordination in rats - Castellanos, Jessika; Eblen-Zajjur, Antonio (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2016)
It is well known that inhibition of Na,K-ATPase by digoxineinduces an increased [Na+]i and [Ca++]i with consequent increasedcell depolarization. This effect has a potential implicationon nociception. To analyze this digoxine effect on painthreshold and neuromuscular activity, 20 male Sprague-Dawleyrats ( 300gr) were treated with NaCl 1mL, 0.9% (Controls,n=10) or digoxine 1mL, 40 μg.Kg-1.day-1 (Digoxine, n=10) i.p.for a week. Daily test was performed for pain threshold by hotplate test (50±0.1ºC, mean±SEM) and neuromuscular motorcoordination by rotarod test (at 17 rpm). Digoxine reduced28% the hot plate latency (17.16±2.05s) when compared tocontrols (23.83±2.32s; P<0,001) and reduces neuromuscularactivity in 95.4% (1.02±5.42s digoxine vs 22.22±5.50s;P<0.001). Both effects were observed from the first doses.There was no correlation neither between hotplate and rotarodtests latencies nor between these values and the accumulativedoses of digoxine. These results strongly suggestthe pronociceptive effect of digoxine by decrease of the thermalpain threshold and that this could be more intense thanreported due to the masking effect of a reduced motor activityduring behavioral tests. The present report contributesto explain recent report of increased pain in digoxine treatedhuman patients.